Abnormal Sexual Behavior During Sleep in an Adolescent: Sexsomnia and Defecation - Oya Güleşen Kapan; Zeynep Ihtiyar Aydilek; Mustafa Kapan; Mehmet Baştemur; Güray Koç; Şahin Bodur; Sinan Yetkin; Mehmet Ayhan Cöngöloğlu (Sleep Science)
Sexsomnia is characterized by sexual behaviors ranging from masturbation, sexual sounds, and verbalizations, to touching and full sexual intercourse during NREM sleep, with subsequent amnesia. Autonomic activation occurs with sexual arousal. Sexsomnia has been described mostly in adult males and is still an underrecognized condition. Treatment is often effective but without current consensus.